Konstruksi Kepercayaan Konsumen pada Wacana Review Skincare Dokter Detektif: Analisis Wacana Kritis Fairclough - Ananda Asmarani; Eti Setiawati (Universitas Muhammadiyah Surakarta, 2026)
The increasing consumption of skincare coincides with the development of the industry, which has fueled competition and fraudulent practices. Amidst these conditions, the discourse of the Dokter Detektif emerges as a source of information and criticism of fraudulent skincare practices. This study aims to uncover how the discourse of the Dokter Detektif skincare review is able to shape consumer trust. The method used is a qualitative descriptive approach with a Fairclough critical discourse analysis approach that focuses on three dimensions, text, discursive practices, and social practices. The research data source is a skincare review video on the TikTok account @dokterdetektifhero with data in the form of the Dokter Detektif speech. Data were analyzed using description, interpretation, and explanation techniques. The results of the analysis show that all three dimensions influence each other in the construction of consumer trust. In the text dimension, the choice of vocabulary and grammar plays a role in displaying ideology, relationships, and evaluative attitudes. Furthermore, discursive practices are formed amidst the conditions of fraudulent practices as a form of education to the public through TikTok. On the social aspect, the Dokter Detektif discourse criticizes illegal practices with his knowledge as a beauty doctor. These three dimensions are interconnected to form an image and credibility that influence consumer trust. Consumers are becoming critical in using the Dokter Detektif discourse as a basis for purchasing decisions.